Clinical Utility of Zuranolone for Postpartum Depression: A Narrative Review - Giannopoulos A; Singh J; Deligiannidis KM (Neuropsychiatric Disease and Treatment, 2025)
Athanasia Giannopoulos,1 Joshna Singh,2 Kristina M Deligiannidis1,3 1Division of Psychiatry Research, Zucker Hillside Hospital, Northwell Health, New York, NY, USA; 2Department of Psychiatry, Jacobs School of Medicine and Biomedical Sciences, University at Buffalo, Buffalo, NY, USA; 3Feinstein Institutes for Medical Research, Northwell Health, Manhasset, NY, USACorrespondence: Kristina M Deligiannidis, Email kdeligian1@northwell.eduAbstract: Peripartum depression (PPD) affects approximately one in every eight birthing individuals. Despite a high prevalence, PPD is underdiagnosed and undertreated. Several PPD treatment options exist including psychotherapies, conventional serotonergic-based antidepressants and alternative and integrative medicine approaches. Rapid-acting neuroactive steroid-based antidepressants have been studied and approved in the United States (US) for the treatment of adult females with PPD. Zuranolone is the first US Food and Drug Administration approved oral antidepressant for adult females with PPD. This narrative review reports on the evidence for the clinical utility of zuranolone in PPD treatment. In double-blind, randomized, placebo-controlled, clinical trials, zuranolone demonstrated rapid, statistically significant and clinically meaningful improvements in depressive symptoms. Most common adverse events reported with zuranolone use were somnolence, dizziness, sedation, and headache. No clinically significant changes in vital signs, electrocardiogram or clinical lab parameters were observed. No loss of consciousness and no increase in suicidal ideation from baseline or deaths were seen in the studies. Secondary analyses demonstrated that zuranolone improves comorbid symptoms of anxiety and insomnia and some measures of health-related quality of life. Zuranolone relevant infant dose lactation data suggest that its use is compatible with breastfeeding, though future research is needed to measure potential adverse effects on the breastfed infant. Key aspects of clinical decision-making in patients with PPD are discussed.Keywords: zuranolone, postpartum depression, neuroactive steroid, GABA, insomnia, anxiety